PEMECAHAN MASALAH NUMERASI KONTEN GEOMETRI DAN PENGUKURAN LEVEL PENALARAN SISWA SMA DITINJAU DARI GAYA KOGNITIF FIELD INDEPENDENT DAN FIELD DEPENDENT - Masrurroh, Aidatul; Rahaju, Endah Budi; Susanah, Susanah (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Minimum Competency Assessment (AKM) of numeracy is one part of the National Examination held by the government today as a replacement for the National Examination. Grønmo (2015) explains the importance of numeracy for students' lives, namely that it can help students solve contextual problems both in the scope of mathematics learning in schools and contexts outside of school. The results of Indonesia's participation in the TIMSS (2015) event were that Indonesia ranked 44th out of 49 countries with a mean numeracy score of 397 from an overall average of 505. It can be said that the numeracy score obtained by Indonesia is far below the overall average. The purpose of this study was to describe the problem solving of geometry content numeracy and measurement of high school students' reasoning levels in terms of the Field Independent (FI) and Field Dependent (FD) cognitive styles of grade XI 8 students at SMAN 1 Krian. The type of research used in this study is descriptive research with a qualitative approach. The sampling technique used a purposive sampling technique with a criterion sampling type in order to select subjects. The instruments for collecting data in this study were cognitive style tests or Group Embedded Figures Test (GEFT) and numeracy problem solving tests (TPMN). All grade XI 8 students were identified for their cognitive style types using GEFT, then one student was taken each representing each type of cognitive style to be given TPMN. Furthermore, the results of TPMN were analyzed and interviews were conducted. The results of the study showed that: 1) students with Field Independent (FI) cognitive style were able to meet the indicators at the stage of understanding the problem, making a plan, and implementing the plan; but were less able to meet the indicators at the stage of re-checking the results, and overall the analytical reasoning level indicators dominated the solving of numeracy problems, 2) students with Field Dependent (FD) cognitive style met the indicators at the stage of understanding the problem and making a plan but were unable to meet the stage of implementing the plan and re-checking the results so that only a few analytical indicators were seen in solving numeracy problems